An Effort of Improving Gross Motor Abilities Through Tarek Pukat Dance in Early Children at Diana Assaffa Islamic Kindergarten Lhokseumawe - Hasanah, Rakiyatul; Nurhayati, Nurhayati; Yusra, Yusra; Ranggayoni, Russy (Jurusan Pendidikan Islam Anak Usia Dini, 2024)
This study aims to improve the gross motor skills of early childhood through the traditional Tarek Pukat dance at TKIT Diana Assaffa Islamic Kindergarten, Lhokseumawe. The research employs a qualitative approach with the Classroom Action Research (CAR) design based on the Kurt Lewin model, consisting of planning, implementation, observation, and reflection stages. Data were collected through interviews, observation, and documentation, and analyzed using descriptive qualitative techniques. The subjects were sixteen children aged 5–6 years in Group B. The findings reveal a significant improvement in children’s gross motor abilities after participating in Tarek Pukat dance activities. In Cycle I, only 31.25% of children reached the expected developmental level, while 12.5% had not yet developed. However, in Cycle II, 81.25% of the children achieved developmental success, with 43.75% categorized as “developed very well.” The improvement demonstrates that Tarek Pukat dance effectively enhances balance, coordination, and rhythmic movement in early learners. The study concludes that integrating local cultural elements, such as traditional dance, into early childhood education provides both developmental and cultural benefits, enriching children’s physical growth while fostering appreciation for local heritage.